2012
DOI: 10.1002/jcp.22976
|View full text |Cite
|
Sign up to set email alerts
|

Diverse effects of type II collagen on osteogenic and adipogenic differentiation of mesenchymal stem cells

Abstract: Type II collagen is known to modulate chondrogenesis of mesenchymal stem cells (MSCs). In this study, MSCs from human bone marrow aspirates were used to study the modulating effects of type II collagen on MSC differentiation during the early stages of osteogenesis and adipogenesis. With osteogenic induction, MSCs cultured on the type II collagen-coated surface showed an enhanced calcium deposition level with increasing mRNA expressions of RUNX2, osteocalcin, and alkaline phosphatase. A synthetic integrin bindi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
20
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(20 citation statements)
references
References 33 publications
0
20
0
Order By: Relevance
“…In turn, many of these characteristics have been shown previously to influence cellular responses to TGF-β3. For example, cellular responses to soluble growth factors can be modulated by insoluble environmental factors such as cell-matrix interactions [52-54] and substrate stiffness [55,56]. In the present study, Day 0 values (data not shown) demonstrated that CDM scaffolds possessed collagen and GAG compositions equivalent to native cartilage [57].…”
Section: Discussionmentioning
confidence: 57%
“…In turn, many of these characteristics have been shown previously to influence cellular responses to TGF-β3. For example, cellular responses to soluble growth factors can be modulated by insoluble environmental factors such as cell-matrix interactions [52-54] and substrate stiffness [55,56]. In the present study, Day 0 values (data not shown) demonstrated that CDM scaffolds possessed collagen and GAG compositions equivalent to native cartilage [57].…”
Section: Discussionmentioning
confidence: 57%
“…Several studies have reported that human MSCs can be induced to enter the osteogenic differentiation pathway in the presence of type I extracellular matrix (ECM) proteins (Salasznyk et al, 2004;Kihara et al, 2006) and type II collagen stimulates (Chiu et al, 2012). COL4A4 was also up-regulated during osteogenic differentiation from rat bone marrow stromal cells (Kaur et al, 2010).…”
Section: Discussionmentioning
confidence: 99%
“…However, we are investigating this different phenotype in future work. What’s more, collagen type II is not the only structural material for the cartilage matrix; it can modulate chondrogenesis and osteogenesis as an extracellular signal molecule [39], [40], [41]. Therefore, alterations of signaling pathways regulating endochondral ossification in the growth plate caused by the ERS-UPR-apoptosis cascade and/or a lack of normal collagen may be a promising research direction.…”
Section: Discussionmentioning
confidence: 99%